2010
DOI: 10.1063/1.3406152
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Faraday rotation effect in heterostructures with magneto-optical metals

Abstract: We theoretically study the transmission and Faraday rotation effect in the heterostructure composed of an all-dielectric photonic crystal and a magnetic metal. Under the tunneling mechanism, the electromagnetic fields can totally enter the structure and localize at the interface between photonic crystal and magnetic metal. Because of the localized electromagnetic fields, the transmission and Faraday rotation in the heterostructure are simultaneously boosted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Moreover, though reduced, the Faraday rotation angle (θ F ≈ −12 o ) is still enhanced by nearly a factor of three in comparison to the standalone MO-metal slab. Overall, the above results are in line with what observed in [18,19], but our configuration is structurally simpler and more compact, its total thickness being only ∼ 0.3λ at the nominal operational wavelength. On the other hand, the Faraday ellipticity (δ F ≈ −0.35), not considered in [18,19], is non-negligible.…”
Section: Realistic Lossy Casesupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, though reduced, the Faraday rotation angle (θ F ≈ −12 o ) is still enhanced by nearly a factor of three in comparison to the standalone MO-metal slab. Overall, the above results are in line with what observed in [18,19], but our configuration is structurally simpler and more compact, its total thickness being only ∼ 0.3λ at the nominal operational wavelength. On the other hand, the Faraday ellipticity (δ F ≈ −0.35), not considered in [18,19], is non-negligible.…”
Section: Realistic Lossy Casesupporting
confidence: 89%
“…More specifically, at optical frequencies, MO metals naturally behave as circularly-birefringent ENG media, whereas an all-dielectric photonic crystal operating in the bandgap region can effectively mimic an MNG-type behaviour [23]. Overall, taking into account realistic losses, multilayers containing a dozen layers (with total thickness of about 1.5 wavelengths) were shown to provide Faraday rotation angles of ∼ 15 o , with transmittance levels ∼ 0.3 that are about an order of magnitude higher than those pertaining to a standalone MO-metal slab [18,19].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that one-dimensional MPCs based on magnetic and nonmagnetic dielectric multilayers realize a huge Faraday rotation angle. [1][2][3][4][5] This MO enhancement originates from the localization of light at selected wavelengths in photonic band-gap structures. Similarly, MO cavities consisting of stacked layer structure enhance the MO effect by multiple re ections of light inside the structure.…”
Section: Introductionmentioning
confidence: 99%
“…13 TPPs have also been proposed for use in switches, 14 and highly efficient, unidirectional transmission in an all-optical diode has been demonstrated using the interface states between a one-dimensional photonic crystal structure of SiO 2 and TiO 2 and a thick layer of silver. 15 TPPs have been shown to exist at an interface between a photonic crystal and a magnetophotonic crystal 16 or a magnetic metal, 17 and the enhancement of Faraday rotation and sharp transmission peaks have been suggested as useful characteristics for magnetotunable filters.…”
Section: Introductionmentioning
confidence: 99%